PROSPECTS FOR USING PUBLIC-PRIVATE PARTNERSHIP MECHANISMS IN FINANCING TELECOMMUNICATIONS INFRASTRUCTURE (International Congress on Economics, Management and Business Studies, 2026)
In today’s economy, telecommunications infrastructure is no longer the material foundation of a single industry but a general economic backbone that ensures the uninterrupted operation of digital services, electronic public administration, distance learning, digital commerce, financial technologies, and information exchange. Accordingly, the task of expanding and renewing this infrastructure has moved beyond a purely technical concern and is becoming a strategic direction that requires financial cooperation between the state and the private sector.